A SOURCE PARAMETERS STUDY OF THE AFTERSHOCK SEQUENCE OF THE KOZANI- GREVENA 1995 EARTHQUAKE BASED ON ACCELERATION RECORDS - Panou, A. A.; Papazachos, C. B.; Papaioannou, Ch.; Hatzidimitriou, P. M. (Bulletin of the Geological Society of Greece, 2004)
Strong motion recordings of the May 13, 1995 Mw=6.6, earthquake sequence that occurred in the Kozani-Grevena region (Western Macedonia, Greece) have been analyzed for the determination of their source parameters. The data set for this study comes from a temporarily deployed accelerograph network and the source parameters using the shear-wave displacement spectra have been estimated. For this estimation the spectral records have been corrected for the site effects and for the propagation path (geometrical spreading and anelastic attenuation). The magnitude of each event was also re-calculated by estimating appropriate station corrections. The derived relationships are logMo =(1.43 ±0.09) M, + (16.92 ± 0.29), 2.0 < ML< 5.0 (1) logfc = (-0.56± 0.08) · ML + (2.52 + 0.29), 2.0 < ML< 5.0 (2) logM0 = (-2.20 + 0.08) · log fc + (23.16 ± 0.84), 0.6 < fc < 10.0 (3) The near-surface attenuation parameter κ0 has also been determined for the strong motion stations sites. These values of κ0 are in good agreement with those of Margaris and Boore (1998) for the geological formation on which each station was positioned. The obtained source parameters are in good agreement with those from previous studies for the Aegean region.